Isolation of stable non cyclic 1,2-disulfoxides: revisiting the thermolysis of S-aryl sulfinimines - Souto, José A.; Lewis, William; Stockman, Robert A. (Royal Society of Chemistry, 2014)
The thermolysis of S-aryl sulfinimines is shown to generate 1,2-disulfoxides and disulfides via initial Cope elimination, dimerisation of the produced sulfenic acid to a thiosulfinate, and subsequent disproportionation of the thiosulfinate.